Perspectives on MADS-box expression during orchid flower evolution and development - Mondragón Palomino, Mariana (Frontiers in Plant Science, 2013)
The diverse morphology of orchid flowers and their complex, often deceptive strategies to become pollinated have fascinated researchers for a long time. However, it was not until the 20th century that the ontogeny of orchid flowers, the genetic basis of their morphology and the complex phylogeny of Orchidaceae were investigated. In parallel, the improvement of techniques for in vitro seed germination and tissue culture, together with studies on biochemistry, physiology, and cytology supported the progress of what is now a highly productive industry of orchid breeding and propagation. In the present century both basic research in orchid flower evo-devo and the interest for generating novel horticultural varieties have driven the characterization of many members of the MADS-box family encoding key regulators of flower development. This perspective summarizes the picture emerging from these studies and discusses the advantages and limitations of the comparative strategy employed so far. I address the growing role of natural and horticultural mutants in these studies and the emergence of several model species in orchid evo-devo and genomics. In this context, I make a plea for an increasingly integrative approach.